Antecedents of health-promoting leadership and workload as moderator - Turgut, Sarah; Sonntag, Karlheinz (Journal of leadership & organizational studies, 2019)
This study builds on the theory of planned behavior and investigates antecedents of health-promoting leadership behaviors (HPL behaviors): positive health-promo...
Gesehen am 27.04.2020